Different responses in one-year-old and three-year-old grass carp reveal the mechanism of age restriction of GCRV infection. Issue 86 (March 2019) - Chen, Geng; Xiong, Lv; Wang, Yumeng; He, Libo; Huang, Rong; Liao, Lanjie; Zhu, Zuoyan; Wang, Yaping
Abstract: Grass carp is an important fish species in Chinese aquaculture, and can be afflicted by a hemorrhagic disease caused by the grass carp reovirus (GCRV). Interestingly, the affects of GCRV infection of grass carp are age-restricted, meaning that one-year-old grass carp can be infected and can suffer hemorrhagic disease, but three-year-old carp are not so afflicted. In this study, we investigated the mechanism responsible for this age-restricted pathology. We evaluated the relative copy number of GCRV RNA, the expression levels of proteins in blood, and changes in DNA methylation in carp from the two age groups after infection with GCRV. After GCRV infection, the relative copy number of GCRV RNA in three-year-old grass carp was significantly lower than in one-year-old carp. The differences in circulating protein levels mainly occurred in concentrated in complement and coagulation proteins, and the expression levels of these proteins were significantly higher in three-year-old grass carp than in one-year-old carp. Moreover, the expression levels of DNA methylation-related genes in the liver and spleen of one-year-old grass carp were significantly higher than those of three-year-old carp. These results suggested that as age of grass carp increases, faster and more efficient response of the immune system after viral infection, especially the complement system, and differences in DNA methylation may be important factors that affect the age restriction observed in GCRV infection. Our study provides new insights into the mechanisms underlying age restriction of GCRV infection. Highlights: The affects of GCRV infection of grass carp are age-restricted. The relative copy number of GCRV in three-year-old grass carp was significantly lower than in one-year-old carp. The expression level of proteins involved in complement and blood coagulation were higher in three-year-old carp. More efficient and faster response of the immune system may contribute to the age restriction of GCRV infection.